A Sustainable Development Council: In the run-up to Rio 2012. Options for reforming the UN sustainability institutions - Marianne Beisheim; Nils Simon; Birgit Lode (Stiftung Wissenschaft und Politik (SWP), 2011)
At the 2012 United Nations Conference on Sustainable Development (UNCSD), the UN institutions that deal with sustainable development are to be restructured. This offers an opportunity to implement long overdue reforms. The planned restructuring should follow the objective to improve the visibility and priority of sustainability themes in the UN system. An important building block in these reforms might be the founding of a Sustainable Development Council (SDC) to replace the politically weak UN Commission on Sustainable Development (CSD). The UN General Assembly could pass a resolution establishing such a council as its subsidiary organ
Keywords: 320